Nature Herb’s Sdn. Bhd / Nurul Ain Abdul Murad... [et al.] - Abd Murad, Nurul Ain; Isa, Iliyana; Hassan, Kamarul Hasnan; Talib, Mohd Zahirruan; Ismail, Mohd Asrul Nizam (2000)
Nature Herb’s Sdn. Bhd is the company use Nonie Fruits as main source to produce alternative medicine that can cure various diseases. The choose of the project is because the vitamin and supplement manufacturing industry will continue to blossom because taking vitamins and other supplements has become a way of life for the ever – growing health conscious and aging population of the society. This company is located at Jejawi Industrial Area, perlis